Climate change and global warming: Critical connection (International Journal of Food and Nutritional Sciences, 2022)
This article examines the central relationship between global warming and climate change, illuminating the complex relationship and its important consequences. Scientific foundations are examined, with a focus on anthropogenic factors such as greenhouse gas emissions and their significant impact on the Earth’s climate. The report highlights immediate atmospheric hazards, changing conditions, sea level rise, and extreme weather, highlighting serious impacts on economies, ecosystems, and public health. It discusses how countries, businesses, governments, and people urgently work together to reduce greenhouse gas emissions and address the growing risks posed by climate change. The findings of this study underscore the critical need for concerted collective action to combat the increasing risks of these interrelated environmental issues.